Direct Detection of Rifampin-Resistant Mycobacterium tuberculosis in Respiratory Specimens Using Quantamatrix Multiplexed Assay Platform (QMAP) System: A Multicenter Study in Korea - Wang, Hye-young; Ahn, Kwangjin; Uh, Young; Lee, Hyeyoung; Kim, Seoyong; Chang, Yunhee; Chang, Chulhun L.; Shim, Tae-sun (Frontiers in Microbiology, 2018)
Rapid and accurate detection of rifampin-resistant Mycobacterium tuberculosis (MTB) is of primary importance for infection control and selection of anti-tuberculosis drugs. The aim of this study was to evaluate the usefulness of a newly developed multiplexed, bead-based bioassay (Quantamatrix Multiplexed Assay Platform, QMAP) for the direct detection of rifampin-resistant MTB in respiratory specimens. A total of 400 respiratory specimens collected from patients with clinically suspected tuberculosis or non-tuberculous mycobacteria (NTM) infections were tested with the culture-based conventional Mycobacterium species identification and QMAP system. Among 400 specimens, 154 samples were evaluated using phenotypic anti-tuberculosis drug susceptibility test (DST) and the QMAP system for the detection of rifampin resistance. Detection agreement rate between the culture-based conventional identification and QMAP system for MTB and NTM according to acid-fast bacillus smear positivity was as follows: 97.0% (131/135) and 93.6% (88/94) in 229 smear-positive samples and 69.4% (25/36) and 73.0% (65/89) in 171 smear-negative samples. Based on culture as the gold standard, the overall sensitivity and specificity of the QMAP system for Mycobacterium identification were 87.3% and 97.8%, respectively. The categorical agreement rate between phenotypic DST and QMAP system for rifampin was follows: complete agreement, 92.9% (143/154); very major error, 0%; and major error, 0.6% (1/154). The overall sensitivity of the QMAP system for the detection of rifampin resistance was 97.1% (34/35). The QMAP system is a useful screening method for the early diagnosis of tuberculosis and selection of anti-tuberculosis drug, as it may detect rifampin-resistant MTB directly from respiratory specimens.